VD_FINDINFO HC / 2012 / 382 vom 7. Mai 2012 - VD Tribunal cantonal (2012)
CONTRAT D'ENTREPRISE, AVIS DES DÉFAUTS, MAÎTRE DE L'OUVRAGE, PRIX DE L'OUVRAGE, DÉFAUT DE LA CHOSE | 363 CO, 367 CO, 370 CO, 308 CPC (CH), 312 al. 1 CPC (CH)